Cysteine‐rich protein 61 regulates adipocyte differentiation from mesenchymal stem cells through mammalian target of rapamycin complex 1 and canonical Wnt signaling. Issue 6 (18th January 2018) - Yang, Yongxu; Qi, Qi; Wang, Yi; Shi, Yaru; Yang, Weili; Cen, Yunzhu; Zhu, Endong; Li, Xiaoxia; Chen, Di; Wang, Baoli
ABSTRACT: Emerging evidence suggests that cysteine‐rich protein 61 (CYR61) plays a role in the differentiation and development of chondrocytes, osteoblasts, and osteoclasts; however, little is known about its role in adipogenesis. The current study indicates that the expression level of Cyr61 was altered in primary cultured marrow stromal cells and the established mesenchymal cell line, C3H10T1/2, after adipogenic treatment. Overexpressing Cyr61 repressed C3H10T1/2 and primary marrow stromal cells to differentiate into mature adipocytes. Conversely, inhibition of endogenous Cyr61 induced C3H10T1/2 and primary marrow stromal cells to fully differentiate. Mechanism investigations reveal that knockdown of Cyr61 inhibited the nuclear translocation of β‐catenin and decreased nuclear protein levels of β‐catenin and transcription factor 7‐like 2. Moreover, the silencing of Cyr61 increased protein levels of phosphorylated ribosomal protein S6 kinase B1, mammalian target of rapamycin, eukaryotic translation initiation factor 4E‐binding protein 1, and ribosomal protein S6—the major components of mammalian target of rapamycin complex 1 (mTORC1) signaling—in C3H10T1/2 cells. Additional investigations demonstrated that treatment with rapamycin significantly attenuated adipocyte formation that was induced by Cyr61 small interfering RNA (siRNA) transfection. Moreover, Cyr61 siRNA also lost its ability to stimulate adipocyte formation under the background of β‐catenin overexpression. Taken together, our study provides evidence that CYR61 regulates adipocyte differentiation via multiple signaling pathways that involve at least the inactivation of mTORC1 signaling and the activation of canonical Wnt signaling.—Yang, Y., Qi, Q., Wang, Y., Shi, Y., Yang, W., Cen, Y., Zhu, E., Li, X., Chen, D., Wang, B. Cysteine‐rich protein 61 regulates adipocyte differentiation from mesenchymal stem cells through mammalian target of rapamycin complex 1 and canonical Wnt signaling. FASEB J. 32, 3096–3107 (2018). www.fasebj.org